High-risk medication errors: Insight from the UK National Reporting and learning system - Abdulrhman Alrowily; Khalid Alfaraidy; Saleh Almutairi; Abdullah Alamri; Wejdan Alrowily; Mohammed Abutaleb; Mohammad Zaitoun; Waddad Sarawi; Mashael Aljead (Exploratory Research in Clinical and Social Pharmacy)
Background: Ensuring patient safety is of paramount importance in healthcare systems. Rising concerns about medical errors in the UK have necessitated a greater focus on studying the nature of such errors, particularly those involving high-risk medications. Objectives: To conduct a retrospective analysis of incidents related to patient safety in the UK based on data from the National Rporting and Learning System (NRLS). Methods: This study was conducted based on a review of the National Reporting and Learning System (NRLS) patient safety reports published between January 1, 2015, and December 31, 2015. NHS Improvement provides details regarding incidents following approval using a data-sharing agreement. In total, 1500 incidents were analszed and equally divided among the three categories of high-risk drugs: opioids, insulin, and anticoagulants. Excel® features and deductive reasoning (thematic analysis) were used for data analysis. Results: The results showed that the insulin category had both the highest risk and most errors compared with anticoagulants and opioids. These errors primarily result from issues related to administering, prescribing, and dispensing the drugs. Inadequate drug checks, communication difficulties among staff and patients, and high staff workloads are often linked to these errors. Conclusion: This study confirms that the NRLS database is a valuable source of data, and the suggestions put forth, based on these results, could contribute to the formulation of measures that diminish the occurrence of errors related to high-risk drugs in healthcare settings. Information technology should enhance medication safety by tracking the process of medication use.